Prática musical coletiva na Orquestra de Metais Lyra Tatuí : contribuições para o desenvolvimento humano - Arruda, Murilo Ferreira Velho de (2016)
This study was made with Lyra Tatuí Brass Orchestra (Orquestra de Metais Lyra Tatuí), a collective music practice project, attending people from 5 to 24 years old which was created in 2002, in Tatuí city, countryside of São Paulo state, Brazil. It was created and developed by the volunteer work of two professional musicians who played in orchestras, started the projetct within the city public schools. In order to join the ensemble, instrument was not needed, neither knowing how to play it, beyond being free. This research sets out to comprehend the educative processes from the group practices of the ensemble that relates to human development of its participants. In a qualitative approach, this research had the field diary as main instrument for data collection, build through participant observation in activities as rehearsals, performances and living together moments between June 2014 and June 2015. The analysis process was made by looking for units in the diaries and grouping them, crating the categories that was discussed from theroretical framework. It is sustained mainly by the Education understanding of the brazilian educator Paulo Freire, and others concepts that dialogue with this perspective, such as Humanizing Music Education (Ilza Joly, Carlos Kater, Hans-Joachim Koellreutter, Mariana Galon, Mariana Ament, Natália Severino, Pedro Dutra, Maria Carolina Joly), Epistemologies of South (Boaventura Souza Santos e Maria Paula Meneses) and Community Music (Lee Higgins). Analysis reveals that both structured music activities, as the moments resulting from these activities bring music, social and human educative processes between educators, participants and community involved. The educative processes such as respect, lovingness, autonomy and commitment are essentially conected with the educative action, in a way that, in music, "tunning an instrument" can encourage or discourage those aspects depending on how it is conducted.